Euro area shadow banking activities in a low-interest-rate environment: A flow-of-funds perspective - Günter Wilfried Beck; Hans-Helmut Kotz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
Very low policy rates as well as the substantial redesign of rules and supervisory institutions have changed background conditions for the Euro Area's financial intermediary sector substantially. Both policy initiatives have been targeted at improving societal welfare. And their potential side effects (or costs) have been discussed intensively, in academic as well as policy circles. Very low policy rates (and correspondingly low market rates) are likely to whet investors' risk taking incentives. Concurrently, the tightened regulatory framework, in particular for banks, increases the comparative attractiveness of the less regulated, so-called shadow banking sector. Employing flow-of-funds data for the Euro Area's non-bank banking sector we take stock of recent developments in this part of the financial sector. In addition, we examine to which extent low interest rates have had an impact on investment behavior. Our results reveal a declining role of banks (and, simultaneously, an increase in non-bank banking). Overall intermediation activity, hence, has remained roughly at the same level. Moreover, our findings also suggest that non-bank banks have tended to take positions in riskier assets (particularly in equities). In line with this observation, balance-sheet based risk measures indicate a rise in sector-specific risks in the non-bank banking sector (when narrowly defined).
urn:nbn:de:hebis:30:3-400616
Keywords: 330; non-bank financial intermediation; shadow banking; financial stability; systemic risk; financial regulation; low interest rate environment